DEVELOPMENT OF A DIGITAL ETHNOBOTANY MODULE BASED ON BANYUWANGI LOCAL WISDOM TO IMPROVE THE SCIENCE LITERACY OF PRESERVICE TEACHERS - Iis Ni'matul Jannah; Dinicen Viclara (SOSIOEDUKASI, 2025)
This research aims to develop a digital teaching module for ethnobotany based on Banyuwangi local wisdom to improve the scientific literacy of prospective biology teacher students at the Universitas 17 Agustus 1945 Banyuwangi. This research uses a development research model, the ADDIE model. ADDIE is an acronym for Analyze, Design, Development, Implementation, and Evaluation. The research subjects consisted of one material expert, one media expert, biology education students taking ethnobotany courses. To see the effectiveness of learning by using the digital teaching module of ethnobotany based on Banyuwangi local wisdom for prospective teacher students, an assessment was used by giving tests before and after learning using the digital teaching module of ethnobotany. The results of the module development have been validated by material and media expert validation and show that this module is very suitable for use in learning in the ethnobotany course. The results of this module development are also quite effective in improving the scientific literacy of prospective biology teacher students when viewed from test scores.